Categories of unbounded operators - Mitchener, P. D. (Methods of Functional Analysis and Topology, 2018)
In this article we introduce the concept of an LK^*-algebroid, which is defined axiomatically. The main example of an LK^*-algebroid is the category of all subspaces of a Hilbert space and closed (not necessarily bounded) linear operators. We prove that for any LK^*-algebroid there is a faithful functor that respects its structure and maps it into this main example.